Wave run-up and response spectrum for wave scattering from a cylinder - Zang, J; Liu, S; Taylor, R; Taylor, P (2008)
Numerical and experimental studies on non-linear wave interaction with a circular cylinder in shallow water were carried out. The effect of non-linearity on the wave run-up on the structure was examined. Numerical predictions from the second order diffraction simulations agreed very well with the experimental measurements for both wave run-up and response spectrum. The second order wave diffraction solution worked well for steep waves in shallow water, while linear diffraction theory incorrectly predicted the peak water levels and response spectrum. This is an abstract of a paper presented at the 18th International Offshore and Polar Engineering Conference (Vancouver, BC, Canada, 7/6-11/2008).